Sosialisasi Kesehatan Reproduksi Pada Remaja SMP Muhammadiyah 61 Tanjung Selamet - Shifah Sagala, Rizqa Auliyah; Laili, Hasanatun; Wanda Harahap, Jesi; Rahmadani Siregar, Mega; Elly Vanda, Medina; Aulia Oktapianti, Wanda (Universitas Muhammadiyah Sukabumi, 2023)
Adolescence is an important period that requires proper knowledge about reproductive health to avoid risks such as unwanted pregnancy, risky sexual behavior, and the spread of HIV/AIDS. This study aims to increase understanding and awareness of adolescent reproductive health at SMP Muhammadiyah 61 Tanjung Selamat through community service activities. Through counseling approaches and interactive discussions, students are provided with information about physical changes, reproductive health, and the impact of unhealthy behaviors. The results of this activity show the high enthusiasm of students in discussions and questions related to reproductive health, indicating the success of the program. This counseling provides a positive first step in equipping students with essential knowledge to make smart decisions related to reproductive health. For the continuation of the program, it is recommended to conduct periodic evaluations, form a team of trained adolescent counselors, and conduct monitoring by accompanying teachers to ensure the application of reproductive health information in students' daily lives. With support from educators and medical personnel, it is hoped that students can develop a better understanding of reproductive health and build a positive attitude towards self-care.